Pain – a Quality Indicator - Červenková, Zuzana; Hlaváčková, Eva; Hodačová, Lenka (University of Pardubice, 2017)
Introduction: The quality and safety of healthcare is currently in the spotlight of experts and non-professionals. The need to implement them into healthcare is related to the supply of healthcare services, the general public pressure on standardizing processes and effectiveness, competition, prestige and last but not least, an effort to avoid patient complaints. Objective: To conduct a pilot study focused on pain observation as a quality indicator; to observe pain management in postoperative patients; to conduct a content analysis of medical records of these patients and to create a checklist for a subsequent in-depth empirical study. Method: A content analysis of medical records focused on compliance and non-compliance with existing policies in the following domains: 1) Records of patients’ pain; 2) Records of medication orders and administration in three phases: I) Patient admission; II) Return to unit; III) First to fourth postoperative day, charting of physicians and nurses. Results: Non-compliance with directives was determined in all observed domains. The most frequent non-compliance was in neglecting pain assessment intervals by nurses. The most dangerous discrepancy was observed between medication orders and their administration. Conclusion: Content analysis of medical records of postoperative patients was conducted and the checklist for subsequent documentation audits was edited. The conclusion of this pilot study will be consulted with the patient care managers and an in-depth empirical study will be conducted based on the results of the present pilot study.
Keywords: analysis of medical records; pain management; quality; safety